The Feasibility of Kangaroo Care and the Effect on Maternal Attachment for Neonates in a Pediatric Cardiac Intensive Care Unit. (June 2021) - Broge, Mary Jane; Steurer, Lisa M.; Ercole, Patrick M.
Abstract : Background: As survival rates in neonates with congenital heart disease have improved, research has shown they are at an increased risk for brain injury and neurodevelopmental delay. One intervention shown to have a positive impact on the development in premature and full-term newborns, as well as a positive impact on mother–infant relationship, is kangaroo care (KC). There is limited evidence to support the use of KC in infants with congenital heart disease, some of who may also be premature. Purpose: The purpose of this study was to examine the safety and feasibility of introducing KC for neonates with congenital heart disease in the pediatric cardiac intensive care unit. Methods: A descriptive observational feasibility study was employed to evaluate the safety and efficacy of KC for this population. Results: There were 25 neonates included with 60 sessions of KC. There were no adverse events including line and tube dislodgments and physiological instability related to the use of KC. Implications for Practice: This study found KC to be safe and feasible for neonates with KC. Implications for Research: This is the first study examining the feasibility and safety of KC in this vulnerable population of neonates. Further research should be conducted using a quasi-experimental design to investigate neurodevelopmental outcomes with a larger sample of patients.